Food policy looking forward from the past - Obenchain, Janel; Spark, Arlene 1945- (Boca Raton, FL CRC Press, 2016)
"Access to safe, adequate, and nutritionally balanced food is a cornerstone of public health. Food Policy: Looking Forward from the Past examines the influences of grassroots movements, the government, and industry on the US food systems. The authors explore the intersection of food and nutrition and how policy influences this overlap. They illuminate how current food policies stem from choices made (or abandoned) along the way. Sprinkled throughout the book are challenging questions meant to evoke critical analysis and inspire further, in-depth exploration. Although the book focuses mainly on policy, it provides enough detailed nutrition information to put the policy discussion in historical context. It examines the emergence of trends, food policies, and legislation balancing issues of food, nutrition and diet-related conditions, such as obesity. It also covers food markets, sustainable agriculture, dietary guidelines and dietary allowances, food labeling, food safety, and school wellness. The book details the nuances of policy discussions and the struggles of the FDA in regulating fortification, food additives, and the development of daily values for nutrients. It also examines themes of government action versus individual liberty. With balanced coverage of nutrition and policy issues, the book illustrates how the past gave rise to the present. It poses many questions, not the least of which is: Do we have the right to know how our food is produced? The balanced coverage of nutrition and policy issues in this book gives you the foundation to critically explore the influence of food policy on public health."-- Provided by publisher.
United States agricultural policies -- Dietary guidance -- Nutrition information policies -- Activism -- Federal food assistance -- Milk -- Meat -- Grains -- Fruits and vegetables -- Enrichment and fortification -- "The nanny state" : taxes, zoning, ordinances, and corporate self-regulation -- Food protection : defense and safety -- Looking forward.
Includes bibliographical references and index.
Keywords: Food consumption -- United States; Food supply -- Government policy -- United States; Food security -- Government policy -- United States; Food -- Safety measures; Food industry and trade -- United States